Glial Cell Engineering in Neural Regeneration - Yao, Li (Springer International Publishing, 2018)
This book focuses on current applications of glial cells in neural regeneration, especially in spinal cord repair. It introduces the application of a few types of glial cells including oligodendrocyte, astrocyte, Schwann cells, and stem cell derived glial cells in neural regeneration. The latest glial cell research with biomaterials, gene modification, and electrical signals is also summarized. This is an ideal book for undergraduate and research students in tissue engineering, neurobiology, and regenerative medicine as well as researchers in the field. This book also: Illustrates the application of glial cells including oligodendrocyte, astrocyte, Schwann cells, and stem cell derived glial cells in neural regeneration Broadens reader understanding of the current applications of glial cells in neural regeneration, especially in spinal cord repair Demonstrates the engineering of glial cells with biomaterials, gene modification, and electrical signals for neural regeneration.